Implementasi Teori Bourdieu Dalam Upaya Menjaga Warisan Budaya Sunan Muria Pada Masyarakat Piji Wetan Desa Lau Kabupaten Kudus - Farid, Muhammad (Jurnal Penelitian, 2021)
AbstractThe cultural heritage of the village is becoming a hot discussion in the midst of such rapid global progress. Among the existing policies, each village is encouraged to have a policy document for the promotion of culture as a basis for development. One of the cultural heritages that is no less interesting is the philosophy of the Tapangeli teachings and Sunan Muria's Pager Mangkok. This can be said as an intangible cultural heritage that underlies the social, economic and cultural behavior of the people in the Muria Region to this day. This research using a qualitative approach, this study aims to narrate social praxis and the efforts made by the people of the Piji Wetan Cultural Village of Lau Village in realizing the above ideals. As a knife of analysis, the researcher uses the bourdieurian theory to reveal the norms and values agreed by the Piji Wetan community in preserving the legacy of Sunan Muria. As a result, the people of the Piji Wetan Cultural Village with the application of their bourdieurian theory won an award from the Indonesian Ministry of Education and Culture as the best cultural village in 2020. Thus, researchers hope that this can inspire academics and social actors who want to advance culture like the Piji Wetan community in Lau Village.